Rancang Bangun Sistem Informasi Penerimaan Murid Baru Berbasis Web pada SMK Sasmita Jaya 2 - Muhammad Yunus Rangkuti; Anggita Tri Sundari; An Najmi As Syfa As Syfa (Jurnal Riset Informatika dan Inovasi, 2026)
This research is motivated by the need for digitalization of administrative procedures at SMK Sasmita Jaya 2. Currently, the school's official website serves as a profile information medium but lacks an integrated system to handle new student registration dynamically. The purpose of this research is to develop a web-based New Student Admission Information System (SPMB) using PHP and MySQL. The system development method is carried out through the stages of needs analysis, database design, and feature implementation. The results show that the developed system is capable of providing registration features, file verification by admins, and automatic report recording in PDF format. The comparison indicates that this new system provides added value in the form of transactional interactivity that was not possessed by the previous school profile website.